Development of the Mr. Klin Laundry Website Using the Waterfall Method for Service Optimization - Yonatan, Kevin; Yusnita, Amelia; Azahari, Azahari (STMIK Widya Cipta Dharma, 2025)
This study aims to develop the Mr Klin Laundry website as a digital solution to improve the effectiveness and quality of services provided to customers. The main problem faced by this business unit is the limitation of ordering processes and service information, which are still carried out manually, thereby hindering service speed, data accuracy, and customer satisfaction. The Waterfall method is used in system development because it consists of structured stages, including requirements analysis, design, implementation, testing, and maintenance. The results of the study show that the developed website is capable of providing online service ordering features, laundry status tracking, pricing information, and customer communication. System testing using black box testing indicates that all functions operate in accordance with the specified requirements. With the presence of this website, service processes become faster, more transparent, and more easily accessible to customers, thereby supporting service optimization and enhancing the competitiveness of Mr Klin Laundry.